Mechanical characterization of base analogue modified nucleic acids by force spectroscopy. Issue 26 (28th June 2021) - Sundar Rajan, Vinoth; Viader-Godoy, Xavier; Lin, Yii-Lih; Dutta, Uttama; Ritort, Felix; Westerlund, Fredrik; Wilhelmsson, L. Marcus
Abstract : Investigating the forces in nucleic acids using single base-pair level modifications and optical tweezers. Abstract : We use mechanical unfolding of single DNA hairpins with modified bases to accurately assess intra- and intermolecular forces in nucleic acids. As expected, the modification stabilizes the hybridized hairpin, but we also observe intriguing stacking interactions in the unfolded hairpin. Our study highlights the benefit of using base-modified nucleic acids in force-spectroscopy.